SIMULATION OF ENERGY CONSUMPTION IN MULTI CLUSTER WIRELESS SENSOR NETWORKS - Pella, S. I. (Jurnal Media Elektro, 2018)
Energy conserving protocols in wireless sensor networks (WSNs), such as S-MAC, introduce multi-cluster network. The border nodes in multi cluster WSNsÂ  have more active time than the other nodes in the network; hence have more energy depletion rate. Since battery replacement in most networks is considered difficult, one or more nodes running out of energy prematurely will affect the network connectivity and decrease the overall network performance severely. This paper aims to (1) analyze the energy consumption in a multi-cluster sensor network and compare it to the single cluster scenario (2) investigate the merging time in a single cluster network. The result shows that, in average the energy needed to deliver a packet in the multi cluster networks is about 150% more than the energy needed in the single cluster networks. Moreover, the merging time in the single cluster networkÂ  using schedule offset as the merging criteria in average is slightly smaller than one in the network using schedule ID as merging criteria.